The impact of the COVID-19 pandemic on the mental health and academic performance of medical postgraduates - Yibo Yu; Yibo Yu; Qiaomei Tang; Qiaomei Tang; Haifei Shi; Ting Chen; Yaping Wang; Hanguang Hu; Ke Yao; Ke Yao (Frontiers Media S.A., 2022)
BackgroundThe Coronavirus disease 2019 (COVID-19) has presented a major challenge to the health, economic, and social sectors of the entire world. This study aimed to investigate the mental health and academic performance of medical postgraduates during the COVID-19 pandemic in China.MethodsA cross-sectional online survey was conducted from March 20 to April 20, 2022 at the Zhejiang University School of Medicine in China. The questionnaire consisted of three parts: general information, mental health and academic performance. Mental health outcomes were assessed according to the Generalized Anxiety Scale (GAD-7) and the Patient Health Questionnaire-9 Scale (PHQ-9).ResultsA total of 153 valid questionnaires were obtained. Of the medical postgraduates in this study, (1) 41.8% had no anxiety symptoms. In addition, 51.0% had mild anxiety symptoms during the COVID-19 pandemic. None of the participants had a severe anxiety or depression disorder; (2) Females experienced significantly more symptoms in mental health measure scores than the males (P < 0.01); (3) 78.4% believed that the COVID-19 pandemic had varying degrees of impact on their academics. Doctoral postgraduates showed greater academic stress, and they were more worried about not meeting graduation standards than the master's postgraduates (P < 0.05). There were no significant differences between the surgical postgraduates and internal postgraduates in either mental health or academic performance.ConclusionsOur study found that the COVID-19 pandemic has had a mild impact on the mental health and academic performance of medical postgraduates in China. Females experienced significantly more symptoms on mental health measure scores than the males. Doctoral postgraduates showed greater academic stress than the master's postgraduates. There is uncertainty regarding how long this COVID-19 situation will persist and increasing recognition that there may be periods of recurrence in the future. We need more active curricular innovation and transformation to maintain and improve medical postgraduates' mental health and academic performance.